Optimal Sizing and Locations of DG Sources in Distribution Systems: A Review of Different Techniques - Abdel-Salam, Mazen; El-Mohandes, Mohamed Th; Yousef, Ali M.; Ramadan, Reham (2019 21st International Middle East Power Systems Conference (MEPCON), 2019)
This paper is aimed at presenting the importance of DG sources in distribution systems and reviewing the published work on optimal planning through determination of optimal locations and sizes of DG sources by minimizing singleobjective function (SOF) and multi-objective function (MOF). The indices of the SOF include active power loss, reactive power loss, bus voltage deviation, voltage stability, cost and others. The MOF combines several indices through weighting coefficients depending on the importance of the indices. The optimization techniques are reviewed after being classified into conventional and artificial-intelligence based-ones. Particular attention is directed to genetic algorithm and its hybrids with other techniques for optimal sizing and location of DG sources.